(untitled) (Baghdad Science Journal, 2018)
In this work, CdS/TiO2 nanotubes composite nanofilms were successfully synthesized via electrodeposition technique. TiO2 titania nanotube arrays (NTAs) are commonly used in photoelectrochemical cells as the photoelectrode due to their high surface area, excellent charge transfer between interfaces and fewer interfacial grain boundaries. The anodization technique of titanium foil was used to prepare TiO2 NTAs photoelectrode. The concentration of CdCl2 played an important role in the formation of CdS nanoparticles. Field emission scanning electron microscopy (FESEM) shows that the CdS nanoparticles were well deposited onto the outer and inner of nanotube at 40 mM of CdCl2. X-ray diffraction (XRD) and energy dispersive X-ray (EDX) analyses were executed for the determination of the composition and crystalline structure of the synthesized samples. Furthermore, the data of EDX confirms the formation of titanium and oxygen for TiO2 nanotubes and cadmium and sulfide for CdS deposits. UV–visible diffuse reflectance spectroscopy (UV-DRS) displayed that CdS nanoparticle which deposited onto TiO2 NTAs causes a red-shift into the visible region. CdS/TiO2 NTAs sample prepared at 40 mM of CdCl2 showed maximum photocurrent of 1.745 mA cm-2 while the bare TiO2 NTAs showed 0.026 mA cm-1.